In vitro elimination of antimicrobials during ADVanced Organ Support hemodialysis - König, Christina; Frey, Otto; Himmelein, Susanne; Mulack, Lisa; Brinkmann, Alexander; Perez Ruiz de Garibay, Aritz; Bingold, Tobias (Frontiers in Pharmacology, 2024)
Background: Acute kidney injury (AKI) requiring continuous renal replacement therapy is common in critically ill patients. The ADVanced Organ Support (ADVOS) system is a novel hemodialysis machine that uses albumin enriched dialysate which allows the removal of protein-bound toxins and drugs. To date, data on antimicrobial removal under ADVOS has not yet been reported.An in-vitro study was conducted using whole porcine blood and continuous infusions of different antimicrobial agents to investigate the effect of ADVOS on drug exposure. Drugs with varying protein binding, molecular weights and renal clearances, anidulafungin, cefotaxime, daptomycin, fluconazole, ganciclovir, linezolid, meropenem and piperacillin were studied.Results: All studied drugs were removed during the in vitro ADVOS experiment. Clearance under ADVOS (CLADVOS) for low protein-bound drugs, such as cefotaxime, fluconazole, ganciclovir, linezolid, meropenem and piperacillin ranged from 2.74 to 3.4 L/h at a blood flow of 100 mL/min. With a doubling of flow rate CL for these drugs increased. Although efficiently removed, this effect was not seen for CLADVOS in high protein-bound substances such as daptomycin (1.36 L/h) and anidulafungin (0.84 L/h).The ADVOS system effectively removed protein-bound and unbound antimicrobials to a significant extent indicating that dose adjustments are required. Further, clinical studies are necessary to comprehensively assess the impact of ADVOS on antimicrobial drug removal. Until clinical data are available, therapeutic drug monitoring should guide antimicrobial dosing under ADVOS.